Epstein–Barr Virus–Induced Cutaneous Diffuse Large B-Cell Lymphoma in a Patient With Angioimmunoblastic T-Cell Lymphoma. (December 2019) - Poon, Flora; Ieremia, Eleni; Collins, Graham; Matin, Rubeta N.
Abstract : Abstract: Cutaneous manifestations of Epstein–Barr virus (EBV)-driven B-cell lymphoid proliferations occur rarely as a result of severe immunodeficiency. To date, only a few cases of extranodal EBV-associated B-cell lymphomas arising in patients with angioimmunoblastic T-cell lymphoma (AITL) have been reported, and less common is a cutaneous presentation. AITL is a rare aggressive tumor that carries a poor prognosis and prompt diagnosis, and recognition of EBV-associated diffuse B-cell lymphoma is essential in these patients to instigate the correct treatment.